2020
DOI: 10.1097/md.0000000000021195
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Target Genes in Hypertension and Left Ventricular Remodeling

Abstract: Introduction: Hypertension occurs profoundly in the world, and left ventricular (LV) remodeling containing functional, structural, and mechanical changes induced by uncontrolled blood pressure is a well-known complication, however the underlying mechanism is still obscure. Methods: To determine differences in gene expression profiles of hypertension and LV remodeling consequence to hypertension, Gene Expression Omnibus 2R online tool was used to identify differently exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
8
1
1
Order By: Relevance
“…Furthermore, we identified 23 differentially expressed probes (DEGs, 2 upregulated genes, and 21 downregulated genes) in peripheral blood cell samples from the GSE74144 dataset (hypertensive patient with normal left ventricular vs. normal control), which was exhibited in Figures 3D , H . Interestingly, we detected few differentially expressed genes in the GSE75360, GSE71994, and part of the GSE74144 datasets based on an absolute 2-fold change with a p -value of < 0.05 ( Figures 3B , C , E , F ), which was contrary to that of Pang et al ( 24 ) who found that 842 DEGs were identified in the GSE71994 dataset (including 629 upregulated genes and 213 downregulated genes), while 28,232 DEGs were identified in the GSE74144 dataset. To account for that contradiction, we continued searching for different publications.…”
Section: Resultscontrasting
confidence: 99%
“…Furthermore, we identified 23 differentially expressed probes (DEGs, 2 upregulated genes, and 21 downregulated genes) in peripheral blood cell samples from the GSE74144 dataset (hypertensive patient with normal left ventricular vs. normal control), which was exhibited in Figures 3D , H . Interestingly, we detected few differentially expressed genes in the GSE75360, GSE71994, and part of the GSE74144 datasets based on an absolute 2-fold change with a p -value of < 0.05 ( Figures 3B , C , E , F ), which was contrary to that of Pang et al ( 24 ) who found that 842 DEGs were identified in the GSE71994 dataset (including 629 upregulated genes and 213 downregulated genes), while 28,232 DEGs were identified in the GSE74144 dataset. To account for that contradiction, we continued searching for different publications.…”
Section: Resultscontrasting
confidence: 99%
“…This gene codes for a subunit of the 26S proteasome complex, which is involved in protein homeostasis. In a gene network analysis, PSMD7 was upregulated in hypertensive patients with LV remodeling compared to those without LV remodeling [ 58 ]. Like GSE1 , the PSMD7 DMR has strong enhancer activity and is an alternative splicing site.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, COQ9 is also a potential biomarker for HTN and HFpEF. Several studies have shown that the expression of Tf and Prnp is altered in many cardiovascular diseases and that Tf and Prnp may be novel biomarkers for HTN and HFpEF ( Gao et al, 2013 ; Rahim et al, 2018 ; Roura et al, 2018 ; Pang et al, 2020 ). Acta1 is involved in the pathological progression of myocardial remodeling ( Pagano et al, 2017 ; Cañes et al, 2020 ), which is closely related to the prognosis of HTN and HFpEF ( Fortuño et al, 2001 ; Georgiopoulou et al, 2010 ; Heinzel et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%